2013
DOI: 10.1111/age.12057
|View full text |Cite
|
Sign up to set email alerts
|

Novel variants in the KIT and PAX3 genes in horses with white‐spotted coat colour phenotypes

Abstract: Variants in the EDNRB, KIT, MITF, PAX3 and TRPM1 genes are known to cause white spotting phenotypes in horses, which can range from the common white markings up to completely white horses. In this study, we investigated these candidate genes in 169 horses with white spotting phenotypes not explained by the previously described variants. We identified a novel missense variant, PAX3:p.Pro32Arg, in Appaloosa horses with a splashed white phenotype in addition to their leopard complex spotting patterns. We also fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 15 publications
1
75
0
3
Order By: Relevance
“…Blue eyes are commonly associated with white markings in a variety of species. Several of the equine KIT variants also show considerable variation in the degree of spotting, including horses with white found only on the head and legs [25,31,32]. Intense selection for the degree of white spotting in the mouse has demonstrated that a large number of additive and modifying loci cumulatively contribute to overall color, in addition to non-genetic factors [33].…”
Section: Resultsmentioning
confidence: 99%
“…Blue eyes are commonly associated with white markings in a variety of species. Several of the equine KIT variants also show considerable variation in the degree of spotting, including horses with white found only on the head and legs [25,31,32]. Intense selection for the degree of white spotting in the mouse has demonstrated that a large number of additive and modifying loci cumulatively contribute to overall color, in addition to non-genetic factors [33].…”
Section: Resultsmentioning
confidence: 99%
“…EDNRB and TRPM1. New mutations, particularly at the KIT and PAX3 loci, are continuously being revealed (Hauswirth et al 2013). The Hucul horses have not been molecularly studied with regard to the genes responsible for the coat colour.…”
Section: Discussionmentioning
confidence: 99%
“…Plenty of mutant alleles at or near the KIT locus were reported to cause a large repertoire of either completely white horses or more or less extensive white-spotting patterns. Apart from the tobiano, the KIT causes sabino-1, roan, doi: 10.17221/7905-CJAS and a few dominant white variants (Haase et al 2009a;Hauswirth et al 2012Hauswirth et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…A study on Dalmatian dogs (Stritzel et al 2009) Also in horses, MITF gene mutations may have pleiotropic effects. Some horses with the so-called "splashed white" coat colour (characterized by a very distinctive large blaze, extended white markings on the legs, and blue eyes) are deaf Hauswirth et al, 2012Hauswirth et al, , 2013. Two mutations were identified that condition the splashed-white phenotype: (Philipp et al, 2011).…”
Section: Mitf Genementioning
confidence: 99%